Muscle blood content and muscle oxygen saturation in response to head down and head up tilt - DURU, ADİL DENİZ; ÇOTUK, HASAN BİROL; AKBAŞ, SAVAŞ; PELVAN, SERDAR ORKUN (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
As microgravity alters blood distribution and flow in muscle tissue, in the present study, blood content and oxygen saturation in extremity muscles were evaluated by an analogous body tilting model. For this purpose, the supine resting posture was compared with successive head down tilt (HDT) and head up tilt (HUT) in ten well trained male volunteers. Muscle oxygen saturation and total hemoglobin content were measured using near infrared spectroscopy sensors attached on the gastrocnemius, vastus lateralis and biceps brachii muscles of each body side. Simultaneously, continuous and noninvasive recordings of arterial blood pressure and heart rate variability were performed. The test protocol consisted of the following stages (5 min each): supine, 6 degrees HDT, 15 degrees HDT, 30 degrees HDT, supine, 6 degrees HUT, 15 degrees HUT, and 30 degrees HUT postures in successive order. The evolution of the rhythmic components in the recorded time series were analyzed by wavelet based multiscale time-frequency distributions, and synchronization between measurement sites by wavelet phase synchronization indexing. A support vector machine (SVM) algorithm was employed for classification of posture in relation to muscle total hemoglobin content or oxygen saturation. Increasing or decreasing gravitational impact due to the posture changes resulted in significant increases or decreases of total hemoglobin content in the muscles, but showed no linear relation to muscle oxygen saturation. This effect was stronger pronounced as the respective extremity part was located more centrifugal to the body tilting axis. Blood pressure and heart rate did not influence muscle oxygen saturation. The two major rhythmic components in the cardiovascular system, the 0.1 Hz and respiratory rhythm, were only weakly displayed in the muscle oxygen saturation time series. Oscillations of muscle oxygen saturation in the very low frequency band displayed left-right synchrony. SVM was able to classify postural changes of muscle blood content with good accuracy but not those of muscle oxygen saturation. These results imply that muscle oxygen saturation during acute postural changes may be mainly regulated by neural drive to the micro-vascular circulation and not by systemic cardiovascular kinetics.
Keywords: Head down tilt; Head up tilt; Muscle oxygenation; Near infrared spectroscopy; Microgravity analog; FLUID SHIFTS; MICROVASCULAR FLOW; MICROGRAVITY